Comparison of Rooftop Garden Elements in Japan and Indonesia. Study case of Ginza Six Garden, Japan, and PIM 3 Garden, Indonesia - Achmad Yozar Perkasa; Dibyanti Danniswari (Universitas Trisakti, 2023)
A rooftop garden is located on the topmost level of a building and provides similar benefits as traditional urban green space while accommodating the limited land issue in cities. The practice of rooftop gardens keeps increasing in urban areas worldwide. There may be differences between rooftop gardens in different countries, be it in the design, the elements, or the activities. This study explores the difference between rooftop gardens in Indonesia and Japan, particularly Jakarta and Tokyo. This study aims to compare the characteristics of rooftop gardens in Jakarta and Tokyo. This study follows a descriptivequalitative approach. The data used in this study is based on visitors’ photos and reviews uploaded to the internet and supported by field observation. PIM 3 Garden’s design concept is based on the trend of citizen culture, which likes to update their activities on social media. In contrast, Ginza Six Garden’s design is based on the Ginza area's history, which combines traditional and modern culture. Since the design concepts are different, the garden elements and the user activities are also different. The main reason for these differences is most likely due to cultural differences. Indonesian people like sharing their activities on social media more than Japanese people. Although the gardens exhibit contrasting designs, elements, and user activities, both seem to accommodate their respective users’ needs and behaviors effectively.